Analisis Prestasi Lampu Petromax Berbahan Bakar LPG - Harmen Burhanuddin (Jurusan Teknik Mesin, Fakultas Teknik, Universitas Lampung, 2011)
In order to decrease subsidy cost of kerosene consumption, Indonesian government right now proposes to convert kerosene to LPG. Consequently, the price of kerosene is expensive in society. LPG can be alternatively used as fuel for the petromax lamp. The use of LPG for the petromax lamp fuel is strongly recommended for sidewalk food sellers as source of light at night if the electricity source is not available. Therefore, it is important to investigate some advantages of the use of LPG as replacing of kerosene for the petromax lamp. The performance of the petromax lamp using LPG as fuel had been carried out with parameters: rate of fuel consumption and light intensity, representing to the need of energy consumption. In the view of economic, the performance of the petromax lamp using LPG was also compared with the performance of petromax lamp using kerosene. The results show that the use of LPG is more clearly efficiency than those of use of kerosene. The fuel energy needed by the petromax lamp to generate lighting is around 224.87MJ/h for kerosene and 213.24 MJ/h for LPG. The energy consumption of LPG is decreased by a factor of 1.05. Economically, the comparison of the price between kerosene and LPG is very significant. The price of kerosene consumption per hour was approximate Rp.941.00, whereas the price of LPG consumption per hour was approximate Rp. 368.00. This shows that if the petromax lamp is operated using LPG for 6 h, the seller foods can save around of Rp 3,438.00. Keywords: petromax lamp, kerosene, LPG, energy consumption.